Praktik MSDM Inovatif dalam Upaya Pembentukan Leadership Bench di PT. Sinergi Kawan Abadi - Budi Satrio Wibowo; Vip Paramarta; Abiyyu Purnanda; Nindi Elis; Ellya Dewi (Universitas Kristen Indonesia Toraja, 2023)
Developing a global leadership bench by advancing human resource management is an important concern for the Company to achieve a sustainable competitive advantage. Therefore, the main objective of this paper is to emphasize the role of transformational leadership of line managers in developing leadership competencies, with theoretical support from transformational leadership theory. For the above purposes, data was collected using a questionnaire and it was found that there is a large influence of line manager transformational leadership in the development of human resource management